2019
DOI: 10.1021/acs.jpcc.9b07080
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Reaction of Methanol on Anatase TiO2(101) Single Crystals and Faceted Nanoparticles

Abstract: Anatase TiO2 is used extensively in a wide range of catalytic and photocatalytic processes. As such, understanding its interactions with prototypical organics such as methanol is of high importance. In this study, we employ a cross-disciplinary approach and study adsorption and dissociation of methanol on the (101) surfaces of anatase TiO2 single crystals (SCs) and faceted nanoparticles (F-NPs). While scanning tunneling microscopy was used to follow the spatial distribution of adsorbed methanol molecules and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 55 publications
2
20
0
Order By: Relevance
“…This suggests that clustering likely occurs transiently when the gas phase (MoO3)n clusters land on TiO2(101). Similar clustering has been observed on TiO2(101) previously for water and methanol at 80 K. [51][52] There, we concluded that the molecules have to be mobile in some sort of precursor state before they chemisorb and become immobile at such low temperatures.…”
Section: Resultssupporting
confidence: 86%
“…This suggests that clustering likely occurs transiently when the gas phase (MoO3)n clusters land on TiO2(101). Similar clustering has been observed on TiO2(101) previously for water and methanol at 80 K. [51][52] There, we concluded that the molecules have to be mobile in some sort of precursor state before they chemisorb and become immobile at such low temperatures.…”
Section: Resultssupporting
confidence: 86%
“…This suggests that clustering likely occurs transiently when the gas phase (MoO3)n clusters land on TiO2(101). Similar clustering has been observed on TiO2(101) previously for water and methanol at 80 K. [52][53] There, we concluded that the molecules have to be mobile in some sort of precursor state before they chemisorb and become immobile at such low temperatures.…”
Section: Resultssupporting
confidence: 86%
“…2,54 This is true for all measured coverages shown in Figure 10b and no changes are observed upon annealing to 450 K. After annealing to 550 K, the Mo 3d spectra reveal an onset of reduction with 9% and 6% contributions from (5+) and (4+) oxidation states at all coverages (observed at 231.0 and 229.6 eV), respectively. [53][54] Further reduction is observed after annealing at 650 K and the extent being slightly higher at low coverages. Interestingly, despite the observed reduction, the annealing did not lead to a decrease in the overall Mo coverage on the surface.…”
Section: Resultsmentioning
confidence: 98%
“…The experiments were performed in an ultrahigh vacuum (UHV) system that has been described previously. , The system, which has a base pressure of ∼1 × 10 –10 Torr, is equipped with a molecular beam source, a closed-cycle helium cryostat for sample cooling, a low-energy electron gun (Kimball Physics, Model ELG-2), a quadrupole mass spectrometer (Extrel, Model EXM720), and a Fourier-transform infrared (FTIR) spectrometer (Bruker, Model Vertex 80) for IRAS measurements performed in external reflection mode. The molecular beam was used to dose water or oxygen.…”
Section: Methodsmentioning
confidence: 99%